Respuesta :

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{ 6(x+y)+y-(x+3)} \end{gathered}$}[/tex]

Put the parentheses using: - (a + b)(= -a -b).

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{-\left(x+3\right)=-x-3 } \end{gathered}$}[/tex]

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{=6\left(x+y\right)+y-x-3 } \end{gathered}$}[/tex]

Expand 6(x+y): 6x+6y.

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x+6y+y-x-3 } \end{gathered}$}[/tex]

Add like elements 6y+y=7y

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x+7y-x-3 } \end{gathered}$}[/tex]

Group Like Terms

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{=6x-x+7y-3 } \end{gathered}$}[/tex]

Add like elements 6x-x=5x.

[tex]\large\displaystyle\text{$\begin{gathered}\sf \bf{\red{=5x+7y-3 \ \ \Rightarrow \ \ \ Answers }} \end{gathered}$}[/tex]

ACCESS MORE